Removal of Pharmaceuticals from Water: Conventional and Alternative Treatments - Otero, Marta; Escapa, Carla; Coimbra, Ricardo N. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Pharmaceuticals represent an especially worrying class of micropollutants because they are biologically active. Thus, their occurrence in aquatic environments may cause undesirable effects in living organisms and, if present in water sources for human consumption, may constitute a public health issue. However, wastewater treatment plants (WWTPs), which have not been designed for the removal of pharmaceuticals and cannot guarantee their full elimination, are considered hotspots for their dissemination in natural waters. In this context, the Special Issue (SI) entitled "Removal of Pharmaceuticals from Water: Conventional and Alternative Treatments" was launched to contribute to the assessment of the contemporary challenges and advances in the removal of pharmaceuticals from wastewater. Papers published in the SI, which have been compiled in this book, approached the topic with either of the following different perspectives: (i) the fate and removal of pharmaceuticals by conventional treatments applied in existing WWTPs; or (ii) advanced and alternative green approaches to remove pharmaceuticals from water. Apart from the Editorial, papers published within this SI include two literature reviews and six experimental studies, all of them presenting unconventional approaches, original views, innovative research and/or novel methodologies. This compilation will definitely spark the attention of readers intrigued in the topic, and is useful for researchers in the field.